AKT (protein kinase B) is implicated in meiotic maturation of porcine oocytes - Kalous, Jaroslav; Kubelka, Michal; Solc, Petr; Susor, Andrej; Motlík, Jan (Reproduction (Cambridge, England), 2009)
The aim of this study was to investigate the involvement of the serine/threonine protein kinase AKT (also called protein kinase B) in the control of meiosis of porcine denuded oocytes (DOs) matured in vitro. Western blot analysis revealed that the two principal AKT phosphorylation sites, Ser473 and Thr308, are phosphorylated at different stages of meiosis. In freshly isolated germinal vesicle (GV)-stage DOs, Ser473 was already phosphorylated. After the onset of oocyte maturation, the intensity of the Ser473 phosphorylation increased, however, which declined sharply when DOs underwent GV breakdown (GVBD) and remained at low levels in metaphase I- and II-stage (MI- and MII-stage). In contrast, phosphorylation of Thr308 was increased by the time of GVBD and reached maximum at MI-stage. A peak of AKT activity was noticed around GVBD and activity of AKT declined at MI-stage. To assess the role of AKT during meiosis, porcine DOs were cultured in 50 microM SH-6, a specific inhibitor of AKT. In SH-6-treated DOs, GVBD was not inhibited; on the contrary, a significant acceleration of meiosis resumption was observed. The dynamics of the Ser473 phosphorylation was not affected; however, phosphorylation of Thr308 was reduced, AKT activity was diminished at the time of GVBD, and meiotic progression was arrested in early MI-stage. Moreover, the activity of the cyclin-dependent kinase 1 (CDK1) and MAP kinase declined when SH-6-treated DOs underwent GVBD, indicating that AKT activity is involved in the regulation of CDK1 and MAP kinase. These results suggest that activity of AKT is not essential for induction of GVBD in porcine oocytes but plays a substantial role during progression of meiosis to MI/MII-stage.
Keywords: Phosphorylation; onkogenní protein v-akt; fosforylace; Female; Phosphatidylinositols; Meiosis; zvířata; Enzyme Activation; Cells, Cultured; dibutyryl cyklický AMP; Bucladesine; oogeneze; oocyty; Swine; meióza; ženské pohlaví; fosfatidylinositoly; kultivované buňky; inhibitory enzymů; Animals; Cell Culture Techniques; aktivace enzymů; Oocytes; Oncogene Protein v-akt; Enzyme Inhibitors; prasata; buněčné kultury; Oogenesis